An Analysis of Speech Act Ability Conducted by the Students of English Department in Muhammadiyah University of Metro - Dedy Subandowo; Mezia Kemala Sari (Journal of English Language Studies, 2017)
This research is entitled The An Analysis of Speech Act Ability Conducted by the Students of English Department at Muhammadiyah University of Metro. It aims to analyze the language strategy and the usage of language politeness toward students’ speech act ability in speaking interaction in Muhammadiyah University of Metro. This is a descriptive qualitative analysis. The population of data is taken from the students of the fifth semester in Muhammadiyah University of Metro. The data collecting technique used in this research is noting technique and participative observation technique. Data analysis technique uses pragmatic identity method. The result of data analysis is presented with informal forms. The results show that there are three kinds of speech act strategy in language communication; namely, 1) locutionary 2) illocutionary, and 3) perlocutionary act. The politeness language usage, however, can be divided into direct and indirect speech and it covers reason, apology, gratitude, and request.  Keywords: Language Politeness Strategy, Sociopragmatics, Speech Act